The electronic transport properties in graphyne and graphyne-like carbon-nitride nanoribbons. (22nd November 2019) - Zhang, Peng-Peng; Peng, Xiao-Fang; Tan, Shi-Hua; Long, Mengqiu; Chen, Ke-Qiu
Abstract: By applying nonequilibrium Green's functions in combination with density-functional theory, we investigate the electronic transport properties of graphyne nanoribbons (GYNR) and graphyne-like carbon nitride nanoribbons (GYCNNR). Our results show that GYNR is a semiconductor and the current across the GYNR system is almost forbidden at low bias voltages, while GYCNNR has a similar metallic band structure and the current shows an obvious negative differential resistance effect. Moreover, the results also show that the Lorenz conductance ratios, namely the ratio of electron thermal conductance and electric conductance against temperature, have different chemical-potential dependence for GYNR and GYCNNR.